Bank Asi Perspective of Yusuf Qardawi and Wahbah Zuhaili - Muhammad Fahmi Aziz Arifin (Journal of Islamic Education, 2026)
A human milk bank is an institution that collects and distributes donated breast milk to infants in need. Its existence has generated debate in Islamic law regarding milk kinship, lineage, and marriage eligibility. This study aims to analyze and compare the views of Yusuf Al-Qaradawi and Wahbah Az-Zuhaili on the legal status of human milk banks. The research employs a library research method with a descriptive-comparative approach. Data were collected from classical Islamic texts, books, and relevant literature and analyzed using content analysis. The findings reveal that Yusuf Al-Qaradawi permits human milk banks because they provide significant benefits for infants and do not establish milk kinship that would prohibit marriage. In contrast, Wahbah Az-Zuhaili considers them prohibited because they may create uncertainty regarding lineage and mahram relationships due to unclear donor identities.